The Human Viewpoint for System Architectures - Handley, Holly A.H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book describes a methodology to represent socio-technical system concerns in the system architecting process. The resulting set of Human Views augments traditional system viewpoints with human-focused data. The Human Viewpoint methodology classifies the socio-technical system context, identifies and collects pertinent data, renders models that can be used for discussion and analysis, and presents the results in Fit for Purpose views that are useful for decision making. The inclusion of the Human Viewpoint during the system architecting stage allows the evaluation of human-system design trade-offs, recognises the impact of the human operator on system performance, and provides the foundation for Human System Integration evaluations during the ensuing system development.
1 Introduction -- 2 Human System Engineering -- 3 Architecture Concepts -- 4 A Socio-Technical Architecture -- 5 Realizing a Human Viewpoint -- 6 Stage 1: Context Development and the Concept View -- 7 Stage 2: Collecting Data and Tasks, Roles and Training Views -- 8 Stage 3: Rendering Models and the Human Network View -- 9 Stage 4: Performing Analyses and the Metrics View -- 10 Stage 5: Fit for Purpose Outcomes and the Constraints View -- 11 Simulation Models - The Human View Dynamics -- 12 Applying Human Viewpoints to Risk-based Decision Making -- 13 Human Performance Modeling of Distracted Driving -- 14 A Human View Approach to Risk Management -- 15 Conclusion: The Human Views Method for Socio Technical Systems. Appendix A- Human View Data for the Commanders Daily Update Brief Example -- Appendix B - Human View SysML Models for React to Contact Example. .
Keywords: Engineering design; Psychology, Industrial; Engineering Design; Work and Organizational Psychology